Potensi Interaksi Obat Antidiabetes Melitus Tipe-2 dengan Obat Antihipertensi - Widy Susanti Abdulkadir; Endah Nurrohwinta Djuwarno; Nur Rasdianah; Juliyanty Akuba; Mimi Fauziah Tahir (Journal Syifa Sciences and Clinical Research, 2023)
The effect caused by the use of antidiabetic and antihypertensive drugs combination needs to be considered. The treatment therapy of the patient has the potential risk of drug interactions that are beneficial or detrimental to the patient. This study aims to determine the potential drug interactions in combinations of antidiabetic and antihypertensive drugs. This research is a descriptive study with a cross-sectional design and retrospective data collection. The sample used is medical records of diabetes mellitus patients with comorbid hypertension from January to December 2021 at Batudaa Public Health Center, Gorontalo Regency. The results showed that there were more female patients than male patients. Based on this study. there were 49 female patients (70%), while the largest age group of 50-59 years included 29 patients (41,43%). Whereas, those with the highest potential for drug interactions were metformin and amlodipine, totaling 54 patients (77%). The mechanism of interaction in this study was the pharmacodynamic phase, and the potential to cause the effect was hypoglycemic through the severity of the interaction was moderate level.Â